Interferon lambda protects the female reproductive tract against Zika virus infection - Caine, Elizabeth A. (Nat Commun, 2019)
Although Zika virus (ZIKV) can be transmitted sexually and cause congenital birth defects, immune control mechanisms in the female reproductive tract (FRT) are not well characterized. Here we show that treatment of primary human vaginal and cervical epithelial cells with interferon (IFN)-α/β or IFN-λ induces host defense transcriptional signatures and inhibits ZIKV infection. We also assess the effects of IFNs on intravaginal infection of the FRT using ovariectomized mice treated with reproductive hormones. We find that mice receiving estradiol are protected against intravaginal ZIKV infection, independently of IFN-α/β or IFN-λ signaling. In contrast, mice lacking IFN-λ signaling sustain greater FRT infection when progesterone is administered. Exogenous IFN-λ treatment confers an antiviral effect when mice receive both estradiol and progesterone, but not progesterone alone. Our results identify a hormonal stage-dependent role for IFN-λ in controlling ZIKV infection in the FRT and suggest a path for minimizing sexual transmission of ZIKV in women.